Thyroid Stimulating Hormone in Patients with Macrocytic Anemia - Aladily, Tariq; Albomhedee, Mohammad; Hakooz, Nancy (Jordan Medical Journal, 2022)
Background Aims: The study aimed to examine the frequency of hypothyroidism among patients with macrocytic anemia and to compare this with the frequency of megaloblastic anemia. Materials and Methods: Routinely transferred specimens for a complete blood count test were sent to the hematology lab in our institution and prospectively screened for high mean cell volume (MCV). A total of 100 cases with macrocytosis were examined for the levels of thyroid stimulating hormone (TSH), vitamin B12 and folate levels. Statistical analysis was performed to investigate a potential association between hypothyroidism and other variables. Results: There were 52 women and 48 men. The range of age was 21–83, with a mean of 59 years. The mean MCV was 104.18 fL, while the mean hematocrit was 35.96%. Fifty-three (53%) patients had anemia. Eighteen (18%) patients had TSH level above the normal range qualifying for hypothyroidism. Among these, eight (44%) had low hematocrit and six (33%) a concomitant megaloblastic anemia. The presence of high TSH level did not show a statistically significant correlation with gender, age, vitamin B12, folate or hematocrit levels. Conclusions: Hypothyroidism is commonly present in patients with macrocytosis. Its frequency is comparable with megaloblastic anemia, and both can occur simultaneously. Routine TSH level testing is recommended in patients with macrocytosis even if hematocrit level is normal or if the patient has megaloblastic anemia.